Rancang Bangun Sistem Informasi Profil Sekolah dan Penerimaan Peserta Didik Baru (PPDB) Online Berbasis Web di MI Negeri 17 Kampus C Pulau Kelapa - Florante Hendrikus Maharia; Hidayah Dwi Tama; Nurul Arif Setiawan (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
MI Negeri 17 Kampus C Pulau Kelapa is a religious-based elementary education institution located in an island region that still disseminates school information conventionally through printed media, announcement boards, and direct communication, resulting in limited reach and slow information distribution. The New Student Admission (PPDB) process is also still conducted manually, from form collection to physical document storage, which risks document damage and loss while slowing down data recapitulation. This study aims to design and build a web-based School Profile Information System and Online PPDB to help the school present information digitally while digitizing the new student admission process. The system was developed using the Waterfall model through five stages: requirements analysis, system design, implementation, testing, and operation and maintenance. Data were collected through direct observation, interviews with school staff, and literature review. The system was modeled using Activity Diagrams, Use Case Diagrams, Sequence Diagrams, and an Entity Relationship Diagram (ERD) normalized to the third normal form, then implemented with a MySQL database. Black-box testing on 20 functional scenarios showed that all features worked as expected with a valid status. The results show that the system successfully transformed the school's information dissemination and admission process from manual to a digital, structured, and accessible online system.